2013
DOI: 10.1002/pmic.201300097
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of cow's milk proteins from the rat intestinal lymph using a proteomic strategy

Abstract: Food proteins were considered to be absorbed into the body after being digested to amino acids, dipeptides, and tripeptides. However, there are studies indicating that some proteins can pass through the intestinal epithelium under normal physiological conditions, perhaps not in sufficient quantities to be of nutritional importance, but in quantities that may be antigenically or biologically active. In the present study, rat intestinal lymph samples were collected using a modified lymph fistula rat model in fas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Due to its resemblance to lipocalin 2, mammalian lipocalins, such as the bovine beta-lactoglobulin BLG, are similarly taken up via the lymphatic system ( 216 , 362 ); in a receptor-mediated fashion and via this route, their ligands will predominantly transport to the residing immune cells. It can even reach the lactal system of nursing mothers and serves as a marker for maternal dietary proteins in breast milk as it is not naturally present in human milk ( 363 ).…”
Section: Allergens or Tolerogens: The Role Of Proteins Carrying Micro...mentioning
confidence: 99%
“…Due to its resemblance to lipocalin 2, mammalian lipocalins, such as the bovine beta-lactoglobulin BLG, are similarly taken up via the lymphatic system ( 216 , 362 ); in a receptor-mediated fashion and via this route, their ligands will predominantly transport to the residing immune cells. It can even reach the lactal system of nursing mothers and serves as a marker for maternal dietary proteins in breast milk as it is not naturally present in human milk ( 363 ).…”
Section: Allergens or Tolerogens: The Role Of Proteins Carrying Micro...mentioning
confidence: 99%
“…uptake is either directly via the lymph 171,173 or can, particularly in combination with lipids, occur via chylomicrons into the lymph system as shown for peanut 174 soy protein, 175 egg proteins, 176,177 and very well-studied for whey proteins. 171,[177][178][179][180] Interestingly, despite that these are food proteins and exogenous, receptor-mediated uptake has been described for a large number of these proteins. [181][182][183][184][185] For many food proteins, fat binding to these proteins (in nut proteins for example) facilitates their lymphatic uptake.…”
Section: Tregmentioning
confidence: 99%
“…Many of the aforementioned food proteins are quite resistant to proteolysis as known for 2S albumins 164 and cupins 165 and for the animal‐derived ovalbumin 166 and lactalbumin, 167 lactoferrins, 168 lipocalin beta‐lactoglobulin, 169 while some of these are sensitive to heat and specific food processing techniques leading to their aggregation 170,171 . They, thus, can maintain their nutrient‐carrying abilities, if not destroyed by proteases or heat‐treatment 172 and their uptake is either directly via the lymph 171,173 or can, particularly in combination with lipids, occur via chylomicrons into the lymph system as shown for peanut 174 soy protein, 175 egg proteins, 176,177 and very well‐studied for whey proteins 171,177–180 . Interestingly, despite that these are food proteins and exogenous, receptor‐mediated uptake has been described for a large number of these proteins 181–185 .…”
Section: Dietary Absorption Of Nutrients: the Bioavailability Differs...mentioning
confidence: 99%
“…Despite evidence showing that numerous foodoriginating peptides can indeed be fully absorbed, it remains true that a significant number of proteins continue to be susceptible to degradation by proteases located on the surface of intestinal microvilli [27]. It has been reported that dipeptides and tripeptides can be absorbed by the body entirely through intestinal endothelial cells [28]. Therefore, the assessment of the durability of ACE-inhibiting peptides during the process of digestion establishes a theoretical foundation for utilizing them as functional elements in food products.…”
Section: Discussionmentioning
confidence: 99%